2016
DOI: 10.1155/2016/2129362
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Support for Pharmacologically Induced Hypoxia in Neonatal Calves

Abstract: Practical methods to provide respiratory support to bovine neonates in a field setting are poorly characterised. This study evaluated the response of healthy neonatal calves with pharmacologically induced respiratory suppression to nasal oxygen insufflation and to continuous positive airway pressure (CPAP) delivered via an off-the-shelf device. Ten calves were randomised to receive either nasal oxygen insufflation (Group 1, n = 5) or CPAP (Group 2, n = 5) as a first treatment after induction of respiratory dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
1
12
0
2
Order By: Relevance
“…Alternatively, the administration of supplementary O 2 may enhance metabolic rate, and consequently increase CO 2 production . Previous studies by our group, of respiratory support in neonatal calves, demonstrated a similar increase in PaCO 2 associated with O 2 supplementation . This effect was attenuated by use of CPAP with ambient air, which was interpreted as suggestive of improved ventilatory efficiency and enhanced gas exchange across the alveolar membrane.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Alternatively, the administration of supplementary O 2 may enhance metabolic rate, and consequently increase CO 2 production . Previous studies by our group, of respiratory support in neonatal calves, demonstrated a similar increase in PaCO 2 associated with O 2 supplementation . This effect was attenuated by use of CPAP with ambient air, which was interpreted as suggestive of improved ventilatory efficiency and enhanced gas exchange across the alveolar membrane.…”
Section: Discussionsupporting
confidence: 51%
“…The experimental design in the current study was intended to control for possible effects associated with treatment order. Although no such effect was observed in Group 1 foals, our previous studies in calves have suggested that treatment order:time interactions are an important experimental consideration and indeed, in Group 2 foals, significant interactions were evident for respiratory rate and CO 2 extraction. Reasons for these differences were not investigated in the current study, but it is possible that cumulative effects of prolonged recumbency were more apparent at T4 than was the case at the earlier sampling time.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Calves that undergo a dystocia are born weak and are often unable to self-ventilate, resulting in respiratory acidosis, hypoxemia, hypothermia, and perinatal mortality ( 3 ). It is imperative that positive pressure ventilation is initiated to overcome the surface tension of unexpanded lungs ( 11 , 18 ). The LMA has been successfully used to ventilate the lungs of humans, cats, dogs, pigs, and rabbits ( 12 , 14 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a human continuous positive airway pressure machine with facial mask was assessed for use in newborn calves with pharmacologically-induced respiratory insufficiency, in a similar study design to the one presented here. However, it only provided modest benefit and required specialized equipment ( 18 ). The LMA and BVM system used in the present study effectively ventilated the calves and the equipment is easily acquired, compact, and portable, and requires minimal maintenance.…”
Section: Discussionmentioning
confidence: 99%